Dose re-evaluation in personal dosimetry using the phototransferred thermoluminescence method of LiF:Mg, Cu, Si TLD. (November 2018) - Kim, Hyoungtaek; Kim, Min Chae; Lee, Jungil; Chang, Insu; Lee, Seung Kyu; Kim, Jang-Lyul
Abstract: Phototransferred thermoluminescence (PTTL) characteristics of LiF:Mg, Cu, Si, developed by the Korea Atomic Energy Research Institute, are presented as part of a simple and reliable method for dose re-evaluation that is compatible with routine personal dosimetry services. A 4.5 mm diameter 0.8 mm thick pellet-type thermoluminescence dosimeter (TLD) was used after dual-step thermal annealing at 300 °C for 10 min, and then at 260 °C for 10 min, in order to obtain thermal stability. For optimal UV illumination, samples were placed under a 254 nm ultraviolet (UV) lamp for 90 min. The PTTL signal was only lower than 2% that of the TL because of low residual signals in high-temperature deep traps. The difference of the PTTL signals between samples appeared up to two times, indicating high variation in the charge density of the deep traps between samples. Various thermal treatments were performed after each PTTL measurement to remove the residual PTTL signal. UV exposure at 250 °C for 20 min fully reset the residual PTTL signals to the same level as that after dual-step annealing. No degradation of the TL peak from repeated thermal treatments was observed until after the eighth treatment when a decrease was noticeable. The measured dose response of PTTL in the range of 1.14–51.3 mGy showed good linearity. The zero dose and minimal detectable dose of the PTTL were 1.36 ± 0.51 mGy and 1.53 mGy, respectively. The attenuation of the PTTL signal resulting from successive TL measurements was recorded to provide a correction factor for quarterly recorded TL measurements applicable to the dose re-evaluation of TLDs in routine personal dosimetry services. Highlights: Dose re-evaluation using LiF:Mg, Cu, Si TLD is possible. Phototransferred thermoluminescence of LiF:Mg, Cu, Si was characterized. Heat treatment is required to remove residual phototransferred thermoluminescence.